Aplicação da análise envoltória de dados na engenharia civil - Felisberto, Leonardo Amaro (Universidade Federal Rural do Semi-Árido, 2020)
In a society marked by high competitiveness due to the emergence of more demanding demands regarding the maintenance and success of organizations, there is an imminence of new approaches that seek to carry out the treatment of specific data and thus evaluate the best efficiency in production processes, through performance sectors and units of organizations. This performance is determined by the financial return provided, in most cases, by the more efficient use of resources in a production process, which can be projected through Data Envelopment Analysis (AED), which will generate an efficiency frontier, and so on, compare them. This study aims to describe the methodology of Data Envelopment Analysis using as a theoretical basis articles, books and dissertations books, which resulted in a work that provides a didactic knowledge about AED and that can be applied in themes related to management in several areas, however, this research investigated only applications in civil engineering. Finally, it is necessary to carry out more up-to-date studies to further enrich the understanding on the topic and consequently promote improvements in organizations.
Monografia
Keywords: Analise Envoltória de Dados; Modelos matemáticos; Gestão; Data Envelopment Analysis; Mathematical models; Management; ENGENHARIAS::ENGENHARIA CIVIL